2006
DOI: 10.1200/jco.2005.02.1923
|View full text |Cite
|
Sign up to set email alerts
|

Successful Chemotherapeutic Modality of Doxorubicin Plus Dacarbazine for the Treatment of Desmoid Tumors in Association With Familial Adenomatous Polyposis

Abstract: A chemotherapeutic regimen of DOX plus DTIC followed by meloxicam is an effective and safe treatment for FAP-associated desmoid tumors. This modality should be considered for use as first-line chemotherapy in symptomatic desmoid tumors that are unresponsive to conventional medical therapy, due to the absence of useful presymptomatic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 22 publications
3
102
0
5
Order By: Relevance
“…Anti-inflammatory agents, hormonal blockade, and cytotoxic chemotherapy also may be useful in selected patients, but overall response rates to these modalities remains modest at best. [23][24][25][26] Investigation of FAP-related desmoids has led to the identification of a potential role for ␤-catenin deregulation in desmoid tumorigenesis. 27 ␤-Catenin is a cadherin-binding protein involved in cell-cell adhesion, but also functions as a transcriptional activator when complexed in the nucleus with members of the T-cell factor/lymphocyte enhancer factor family of proteins.…”
mentioning
confidence: 99%
“…Anti-inflammatory agents, hormonal blockade, and cytotoxic chemotherapy also may be useful in selected patients, but overall response rates to these modalities remains modest at best. [23][24][25][26] Investigation of FAP-related desmoids has led to the identification of a potential role for ␤-catenin deregulation in desmoid tumorigenesis. 27 ␤-Catenin is a cadherin-binding protein involved in cell-cell adhesion, but also functions as a transcriptional activator when complexed in the nucleus with members of the T-cell factor/lymphocyte enhancer factor family of proteins.…”
mentioning
confidence: 99%
“…Reports have suggested that therapy might be associated with an initial benefit but the long-term clinical improvement is minimal [39][40][41] . Cytotoxic chemotherapy (doxorubicin, dacarbazine, and carboplatin) may be effective in treating aggressive, rapidly growing and unresectable abdominal desmoids [42,43] . Radiation therapy might be effective in selected cases but it is frequently limited by the presence of the small bowel in the radiation field in mesenteric and pelvic desmoids [44,45] .…”
Section: Managementmentioning
confidence: 99%
“…Dacarbazine (DTIC)-doxorubicin (DOX) therapy (D-D therapy) is a hopeful therapeutic option against desmoid tumors, providing a high clinical response (8)(9)(10)(11)(12). DOX interferes with the function of topoisomerase II and DTIC is an N-methyl-type compound that produces alkylating species.…”
Section: Introductionmentioning
confidence: 99%